Factor Affecting the Production Decisions of Safety Vegetables by Farming Households: Empirical Research in the Midland and Northern Mountainous Regions of Vietnam - Giang, Ngo Thi Huong; Huong, Duong Thi Thuy; Hoa, Ha Thi Thanh; Trang, Vo Thy (Journal of Posthumanism, 2025)
The sustainability of the fruit and vegetable industry has been threatened by the indiscriminate use of agricultural chemicals to enhance commercial production. Implementing Good Agricultural Practices (GAP) can help minimize chemical use in commercial vegetable farming. This study uses a quantitative approach to examine how various factors influence both the initial adoption and continued compliance with GAP among Vietnamese farmers. Using a structural equation modeling (SEM) approach, the research analyzes data from 214 vegetable-growing households across 14 provinces in Vietnam’s northern midland and mountainous regions. The findings indicate that subjective norms, perceived behavioral control, and communication positively impact farmers' decisions to adopt GAP. However, environmental awareness among farming households does not significantly affect their decision to adopt GAP in safe vegetable production. This study contributes to the theoretical framework and practical applications in the agricultural sector, offering farmers valuable insights into GAP adoption. It also highlights that the beliefs of farming households play a crucial role in the successful implementation of GAP in safe vegetable production.